Penerapan Video Pembelajaran Berbasis Kearifan Lokal dalam Meningkatkan Kompetensi Guru Sosiologi di SMA Negeri 1 Seram Bagian Barat - Merti Seska Rosely; Yandri Tuarissa; Nurwati Tamrin (BADAN PENERBIT STIEPARI PRESS, 2026)
This study aims to examine the meaning contained in the Cakalele dance ritual as a local wisdom of the Maluku tribe that can be used as a source for sociology learning at the high school level or equivalent. Sociology, as a social science, can utilize this local wisdom to enrich understanding and help students understand sociology learning themes. This study used descriptive qualitative research. Data collection was conducted through non-participant observation, in-depth interviews, and documentation. Data analysis used interactive techniques. The results of the study can be conveyed that learning management in the local wisdom of the